The Orthoptera (Ensifera) from the Santana formation (Early Cretaceous, Northeast Brazil): A statistical and paleoecological approach, with description of new taxa - Martins-Neto, Rafael Gioia; Tassi, Lara Vaz (Zootaxa, 2009)
This paper on the Araripe orthopterofauna reviews the Cearagryllus-like Grylloidea (Orthoptera: Ensifera) from the laminated limestone of the uppermost part of the Crato Member, lowest unit of the Santana Formation (Early Cretaceous), Araripe Basin, near Santana do Cariri and Nova Olinda municipalities (Ceará State, Northeast Brazil). The following new taxa are proposed: Notocearagryllus arturandradai n. sp., Cryptocearagryllus revelatus n. gen. et n. comb., Allocearagryllus leipnitzi n. gen et n. comb., Cearagrylloides perforatorius n. gen. et n. comb., Cearagrylloides microcephalus n. gen. et n. comb., Cearagrylloides previstus n. gen. et n. comb., and Paracearagryllus poliacanthus n. gen. et n. comb. (Cearagryllinae n. subfam.). Additionally new data on the paleoecology and paleoethology are furnished as well as a statistical approach.